Evaluating the impact of implementing evidence-based practice - Bick, Debra; Graham, Ian D.; Sigma Theta Tau International (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell ; [Indianapolis, Ind.] : Sigma Theta Tau International Honor Society of Nursing, 2010)
"'Evaluating the impact of implementing Evidence-Based Practice' is the third of three books on implementing evidence based practice in the Evidence-based nursing series published jointly by Blackwell Publishing and Sigma Theta Tau International. 'Evaluation and outcome measures for evidence-based practice' addresses the means to rigorously identify, evaluate and assess the outcomes of implementation of evidence into practice. 'Evaluating the impact of implementing Evidence-Based Practice' provides practical and effective guidance on how to assess whether implementation was effective, the full range of issues to be considered when measuring the impact of implementation and the range of approaches which could be used. It stresses the importance of ensuring the long-term sustainability of improvements in care and of measuring the use of interventions and innovations, in order to effectively evaluate the impact on outcomes and. It examines the impact of implementation on economic outcomes and the outcomes of importance to different groups including service users, clinicians, managers and policy makers. The approaches outlined in each chapter are transferable across a range of international, professional and healthcare settings"--Provided by publisher.